Monitoring the electric field in CdSe quantum dots under ultrafast interfacial electron transfer via coherent phonon dynamics. Issue 47 (26th November 2018) - Cherepanov, Dmitry A.; Gostev, Fedor E.; Shelaev, Ivan V.; Denisov, Nikolay N.; Nadtochenko, Victor A.
Abstract : Quantum-confined Stark and Franz–Keldysh effects in CdSe/MV 2+ QDs were monitored in coherent phonon dynamics accompanying ultrafast electron transfer. Abstract : Coherent phonon dynamics in CdSe quantum dots (QD) under an ultrafast electron transfer (ET) reaction of the (1Se –1S3/2 ) exciton quenched by methyl viologen (MV 2+ ) adsorbed onto the QD surface was studied by ultrafast pump–probe spectroscopy. Frequency and amplitude modulations (FM, AM) of the transient absorption Δ A ( ω probe, t ) in the pure CdSe and coupled CdSe/MV 2+ QDs were identified in the bleach band dynamics of the red-edge exciton. The fast Fourier transform (FFT) and continuous wavelet transform analysis of the FM and AM oscillations revealed peaks at 0.51–0.58 THz (17–19 cm −1 ) and 6.06–6.27 THz (202–209 cm −1 ) attributed to the longitudinal acoustic (LA) and longitudinal optical (LO) phonons, respectively. The electron transfer to MV 2+ proceeded non-exponentially with effective time constants of 164 fs (∼30%) and 540 fs (∼70%). The quantum yield of MV˙ + radical formation was 40 ± 5%. It implies a fast route for the electron–hole pair [h + …MV˙ + ] recombination that can be rationalized in accordance with the adiabatic ET mechanism at the semiconductor surface. In the coupled CdSe/MV 2+ QDs, the amplitude of the FM oscillations rose considerably with time despite the natural attenuation of the phonon amplitude due to decoherence processes. A kinetic model explaining the increase of FM oscillations is proposed. The surprising growth of FM oscillations is elucidated by the kinetic model taking into account the relatively slow damping of LO phonon oscillations (∼1.5 ps), the ultrafast ET to MV 2+, and the quantum yield of charge separation [h + …MV˙ + ] (∼40%). The fast formation of the charge-separated pair [h + …MV˙ + ] suggests the appearance of an electric field F with a strength of ∼3 × 10 6 V cm −1 . The MV 2+ reduction substantially increased the magnitude of LA phonon oscillations. Since the ET time is shorter than the period of LA phonon oscillations (∼1.8 ps), the MV 2+ reduction substantially increased the magnitude of LA phonon oscillations due to the inverse piezoelectric effect. The CdSe nanocrystals exposed to the electric field F exhibit the quantum-confined Stark and Franz–Keldysh electro-absorption effects. The proposed kinetic model gives consideration to the dynamic Stark shift of the red-edge exciton and to the increased amplitude of LO phonon oscillations in the bleach band dynamics.